Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics

First principles calculations of thermal, equations of state and thermodynamical properties of MgH2 at finite temperatures - Kelkar, Tuhina; Kanhere, Dilip G.; Pal, Sourav (Computational Materials Science, 2008)
We present the first principles calculations of the thermodynamical properties of magnesium hydride (MgH2) over a temperature range of 0-1000 K. The phonon dispersions are determined within the density functional framework and are used to calculate the free energy of MgH2 within the quasiharmonic approximation (QHA) at each cell volume and temperature T. Using the free energies the thermal equation of state (EOS) is derived at several temperatures. From the thermal EOS structural parameters such as the equilibrium bell volume (V-0) and elastic properties, namely, bulk modulus (K-0) and its pressure derivative (K-0(')) are computed. The free energies are also used to calculate various thermodynamical properties within QHA. These include internal energy E, entropy S, specific heat capacity at constant pressure C-P, thermal pressure P-thermal(V,T) and volume thermal expansion Delta V/V (%). The good agreement of calculated values of S and Cp with experimental data exhibits that QHA can be used as a tool for calculating the thermodynamical properties of MgH2 over a wide temperature range. P-thermal(V,T) increases strongly with T at all the volumes but it is a slowly varying function of volume for T = 298-500 K. According to Karki [B.B. Karki, Am. Miner. 85 (2000) 1447] such volume based variations can be neglected and so it is possible to estimate the thermal EOS only with the knowledge of the measured P-thermal(V,T) versus temperature at ambient pressure and isothermal compression data at ambient temperature. Temperature dependence of Delta V/V(%) shows that V-0 increased with increase in temperature. However, the percentage decrease in K-0 superseded this percentage increase in V-0 even at temperatures moderately higher than 298 K. Therefore, we suggest application of temperature (T > 298 K) as an approach to enhance the hydrogen storage capacity of MgH2 because of its better compressibility at these temperatures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: equation of state; Hydrogen storage; lattice dynamics; magnesium hydride; Thermodynamic properties

Model study of effect of M = Li+, Na+, Be2+, Mg2+, and Al3+ ion decoration on hydrogen adsorption of metal-organic framework-5 - Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2010)
The effect of light metal ion decoration of the organic linker in metal organic framework MOF 5 on its hydrogen adsorption with respect to its hydrogen binding energy (Delta B E) and gravimetric storage capacity is examined theoretically by employing models of the form MC6H6 nH(2) where M = Li+ Na+ Be2+ Mg2+ and Al3+ A systematic investigation of the suitability of DFT functionals for studying such systems is also carried out Our results show that the interaction energy (Delta E) of the metal ion M with the benzene ring Delta B E and charge transfer (Q(trans)) from the metal to benzene ring exhibit the same increasing order Na+ < Li+ < Mg2+ < Be2+ < Al3+ Organic hnker decoration with the above metal ions strengthened H-2 MOF 5 interactions relative to its pure state However amongst these ions only Mg2+ ion resulted in Delta B E magnitudes that were optimal for allowing room temperature hydrogen storage applications of MOF 5 A much higher gravimetric storage capacity (6 15 wt % H-2) is also predicted for Mg2+ decorated MOF 5 as compared to both pure MOF 5 and Li+ decorated MOF (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: Binding energy; Hydrogen adsorption; Hydrogen storage; Metal organic frameworks

Ab initio and periodic DFT investigation of hydrogen storage on light metal-decorated MOF-5 - Dixit, Mudit; Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2011)
The effect of light metal (M = Li, Be, Mg, and Al) decoration on the stability of metal organic framework MOF-5 and its hydrogen adsorption is investigated by ab initio and periodic density functional theory (DFT) calculations by employing models of the form BDC:M-2:nH(2) and MOF-5:M-2:nH(2), where BDC stands for the benzenedicarboxylate organic linker and MOF-5 represents the primitive unit cell. The suitability of the periodic DFT method employing the GGA-PBE functional is tested against MP2/6-311 + G* and MP2/cc-pVTZ molecular calculations. A correlation between the charge transfer and interaction energies is revealed. The metal-MOF-5 interactions are analyzed using the frontier molecular orbital approach. Difference charge density plots show that H-2 molecules get polarized due to the charge generated on the metal atom adsorbed over the BDC linker, resulting in electrostatic guest-host interactions. Our solid state results show that amongst the four metal atoms, Mg and Be decoration does not stabilize the MOF-5 to any significant extent. Li and Al decoration strengthened the H-2-MOE-5 interactions relative to the pure MOF-5 exhibited by the enhanced binding energies. The hydrogen binding energies for the Li- and Al-decorated MOF-5 were found to be sensible for allowing reversible hydrogen storage at ambient temperatures. A high hydrogen uptake of 4.3 wt.% and 3.9 wt.% is also predicted for the Li- and Al-decorated MOF-5, respectively. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ab initio calculations; Density functional theory; Hydrogen binding energies; Hydrogen storage; Metal-Pi-Arene interactions